Excessive use of the Internet on the mental health of nursing university students - Heber Nehemias Chui Betancur; Máximo Valdivia Arias (O Mundo da Saúde, 2023)
Internet use has grown by 4% by 2023 and has become a fundamental tool in our everyday lives, however, its excessive use can contribute to mental health problems such as anxiety, depression and burnout, especially in university health students. This study aimed to determine the risk of anxiety and burnout due to excessive internet use in university nursing students. The research had a non-experimental quantitative approach, with an explanatory design. The study had the participation of 337 nursing students from the Universidad Privada San Carlos SAC de Puno, with an average age of 30.35 ± 9.274 years; 15.70% (n=53) were men and 84.30% (n=284) were women. Students who used the internet excessively for more than four hours a day had a 3.160 times greater risk of developing anxiety (95% CI: 1.519-6.577); 1.704 times more likely to develop emotional exhaustion (95% CI: 0.925-3.215); 1.786 times more likely to develop depersonalization disorders (95% CI: 0.931-3.413) and 2.101 times more likely to develop a lack of personal fulfillment compared to students who use the internet for less than three hours a day. Anxiety levels are positively associated with emotional exhaustion (rho=0.765; p<0.001); depersonalization (rho=0.744; p<0.001); lack of personal fulfillment (rho=0.631; p<0.001), which indicates that excessive internet use by university students had harmful negative effects on mental health.